Analysis of Student Satisfaction with The Quality of Services in Physics Learning in The Implementation of The Independent Curriculum - Hasbullah, Fahmi; Arafah, Kaharuddin; Mansyur (Pascasarjana, Mataram University, 2025)
This study is a quantitative descriptive study that aims to examine the level of students’ satisfaction on the quality of Physics learning services in the implementation of Merdeka (independent) curriculum at UPT SMAN 2 Makassar. The research population was 360 ​​ grade X students. The sampling used in the study was the proportional cluster random sampling technique and obtained a sample of 300 students. Data collection used a questionnaire with a Likert scale model. The data analysis used was Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results of the IPA analysis reveal that the quality of educational services in the tangible (physical evidence) and reliability dimensions at UPT SMAN 2 Makassar, the service quality is so-so and considered less important by students, so the handling is in low priority. In the dimensions of assurance, empathy, and responsiveness, the service quality needs to be maintained because the reality discovered is in accordance with the students’ expectations. The results of the CSI analysis obtained a value of 75.57%, indicating that the students’ satisfaction on the quality of Physics learning services in the implementation of Merdeka curriculum at UPT SMAN 2 Makassar is in